PENGARUH STORE ATMOSPHERE CAFETARIA, VARIASI PRODUK, DAN HARGA TERHADAP MINAT BELI KONSUMEN - Fitriyani, Liza; Mulyati, Awin; Andayani, Sri (Universitas 17 Agustus 1945 Surabaya, 2018)
In This study to determine to effect of atmosphere stores, product Variation and Price to Consumer buying interest in Food Coma Daily Cafetaria. Where independent variables are Store Atmosphere (X1), Product Variation (X2), and Price (X3) influence Consumer buying interest (Y). in this population are all consumer of Food Coma Daily Cafetaria samples taken as many as 100 respondent. This sampling method used in Non Random Sampling Method. Then done the analysis through data obtained by using data analysis quantitative. This analysis includes: test of validity, reliability, multiple liner analysis, hypothesis test through t test, F test coefficient of determination analysis (R2).Based on the research has fulfiled the validity and reliability test by obtaining the regression equation as follow: Y = 0,047+ 0,157(X1) + 0,419(X2) + 0,414(X3). Testing t test hypothesis shows that variable Store Atmosphere no significant effect on consumer buying interest. based on the results of this study suggested that Food Coma Daily Cafetaria still maintain the benefits of Store Atmosphere is adequate because some consumers decided to buy because Store Atmosphere and still make one of the main goals because it has a major impact on subsequent purchases. And variable Product Variation and Price significantly influence consumer interest. then F test can know that the three independent variables are meticulous simultaneously affect the dependent variable consumer buying interest can be explained by Store Atmosphere, Product Variation and Price while the rest 52,6% . so the rest factora beyond other variables in this study.Keyword: Store Atmosphere, Product Variations, Price and Consumer buying interest